If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25 = 10 + 5j Solving 25 = 10 + 5j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-5j' to each side of the equation. 25 + -5j = 10 + 5j + -5j Combine like terms: 5j + -5j = 0 25 + -5j = 10 + 0 25 + -5j = 10 Add '-25' to each side of the equation. 25 + -25 + -5j = 10 + -25 Combine like terms: 25 + -25 = 0 0 + -5j = 10 + -25 -5j = 10 + -25 Combine like terms: 10 + -25 = -15 -5j = -15 Divide each side by '-5'. j = 3 Simplifying j = 3
| 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 | | (r-p)/(x-q)=m | | -5x-(-3*-13)=30 | | 2x-4-6=0 | | 12+[6+(13-7)]2-5= | | 72/4.8=20.4/c | | -(x-8)+4=2(-1)+x | | y+4.3=5.9 | | 42x^2-40x+8=0 | | 5k^2+35k+60=0 | | -(x-8)+4=2(1.25)+x | | 12/x=7/3 | | -(x-8)+4=2(0)+x | | 3(2p+7)=1 | | 7/n=24.5/56 | | 7(1-5r)+6r=94 | | 6(9x+2)=54x-7 |